Gait Analysis and Trajectory Planning of Quadruped Wheel-legged Mobile Robot - Qing Li; Liting Zhao; Yuxi Feng; Rongshuai Liu; Peng Zhang (Jixie chuandong)
A quadruped wheel-legged mobile robot based on 2-UPS/（S+SPR）R closed loop parallel mechanism is designed for the complex surface environment of aliens planet. The optimal gait is obtained by comparing the stability margin and the barycenter adjustment of the robot in the process of motion， the stability of the robot in the static gait is measured by ZMP method， and the trajectory of the foot end is planned by the improved compound cycloid method. In the whole movement process， the movement of the mechanical leg is stable and the change of speed and acceleration is relatively smooth， which would not cause damage to the mechanical leg due to strong impact. Besides， the speed and acceleration are zero at the moment of lifting the leg and landing， which would not impact the fuselage. The analysis results indicate that the quadruped wheel-legged mobile robot moves flexibly and smoothly， which is suitable for the exploration of outer space.